Light to Moderate Alcohol Consumption Is Protective for Type 2 Diabetes Mellitus in Normal Weight and Overweight Individuals but Not the Obese. (22nd July 2014) - Metcalf, Patricia A.; Scragg, Robert K. R.; Jackson, Rod
Abstract : Objective . To examine the association between alcohol consumption and risk of type 2 diabetes mellitus (T2DM) overall and by body mass index. Methods . Cross-sectional study of employed individuals. Daily alcohol intakes were calculated from a self-administered food frequency questionnaire by 5, 512 Maori, Pacific Island, and European workers (3, 992 men, 1520 women) aged 40 years and above. Results . There were 170 new cases of T2DM. Compared to the group with no alcohol consumption and adjusting for age, sex, and ethnicity, the group consuming alcohol had relative risks of T2DM of 0.23 (95% CI: 0.08, 0.65) in normal weight individuals, 0.38 (0.18, 0.81) in overweight individuals, and 0.99 (0.59, 1.67) in obese individuals. After further adjusting for total cholesterol, HDL-cholesterol, triglycerides, smoking habit, physical activity, socioeconomic status, body mass index, and hypertension, the relative risks of T2DM were 0.16 (0.05, 0.50) in normal weight individuals, 0.43 (0.19, 0.97) in overweight individuals, and 0.92 (0.52, 1.60) in overweight individuals. Across the categories of alcohol consumption, there was an approximate U-shaped relationship for new cases of T2DM. There was no significant association between alcohol consumption and IGT. Conclusions . Alcohol consumption was protective against diagnosis of T2DM in normal and overweight individuals but not in the obese.